2022
DOI: 10.3390/jcm11082145
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potentially Pathogenic Variants Associated with Recurrence in Medication-Related Osteonecrosis of the Jaw (MRONJ) Patients Using Whole-Exome Sequencing

Abstract: Background: Bisphosphonates are antiresorptive and antiangiogenic drugs that prevent and treat bone loss and mineralization in women with postmenopausal osteoporosis and cancer patients. Medication-related osteonecrosis of the jaw (MRONJ) is commonly caused by tooth extraction and dental trauma. Although genetic and pathological studies about MRONJ have been conducted, the pathogenesis of MRONJ still remains unclear. Methods: We aimed to identify genetic variants associated with MRONJ, using whole-exome sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…Consistent with the results in this work, the SIRT1 gene SNP rs932658 has also been demonstrated to be in association with MRONJ by regulating SIRT1 expression [17]. Other research groups have suggested potential roles of SNPs in the VEGF, CYP2C8, PPARG and other genes in the development of MRONJ [19,[24][25][26][27].…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with the results in this work, the SIRT1 gene SNP rs932658 has also been demonstrated to be in association with MRONJ by regulating SIRT1 expression [17]. Other research groups have suggested potential roles of SNPs in the VEGF, CYP2C8, PPARG and other genes in the development of MRONJ [19,[24][25][26][27].…”
Section: Discussionsupporting
confidence: 89%
“…[12][13][14] Using whole-exome sequencing, PABPC3 was found to be related to recurrence in patients with medication-related osteonecrosis of the jaw. 15 However, the interconnection between PABPC3 and osteosarcoma has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…mRNA polyadenylation, nonsense‐mediated decay, stress response, controlling mRNA translation initiation, mRNA quality surveillance and many other mRNA homeostasis‐related processes are regulated by the multifunctional proteins known as PABPs 12–14 . Using whole‐exome sequencing, PABPC3 was found to be related to recurrence in patients with medication‐related osteonecrosis of the jaw 15 . However, the interconnection between PABPC3 and osteosarcoma has not been explored.…”
Section: Introductionmentioning
confidence: 99%